REDEFINING MOTHERHOOD IN EARLY 20TH-CENTURY BUMIPUTERA WOMEN'S PRESS: Redefinisi Keibuan Dalam Pers Perempuan Bumiputera Awal Abad Ke-20 - Zellica Vanudia Amundari (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
In the early 20th century, the emergence of the Bumiputera women’s press became a crucial medium for redefining the roles and identities of women within the colonial society of the Dutch East Indies. This article examines how the concept of motherhood was constructed, negotiated, and redefined through print media managed by and aimed at Bumiputera women. Employing a cultural historical approach combined with discourse analysis, this study explores the construction of motherhood within the contexts of colonialism, early nationalism, and modernity. It reveals that the figure of the